EUS-guided Gastrojejunostomy Versus Laparoscopic Gastrojejunostomy: An International Collaborative Study. Issue 10 (November 2017) - Perez-Miranda, Manuel; Tyberg, Amy; Poletto, Daniel; Toscano, Ernesto; Gaidhane, Monica; Desai, Amit P.; Kumta, Nikhil A.; Fayad, Lea; Nieto, Jose; Barthet, Marc; Shah, Raj; Brauer, Brian C.; et al.
Abstract : Introduction: Endoscopic ultrasound–guided gastrojejunostomy (EUS-GJ) with placement of a lumen-apposing metal stent is a minimally invasive and efficacious procedure for gastric outlet obstruction (GOO) patients not amenable to surgery. Laparoscopic gastrojejunostomy (Lap-GJ) has traditionally been the standard of care. No direct comparison between EUS-GJ and Lap-GJ has been described. Our aim was to compare the clinical outcomes, success rate, and adverse events (AE) of EUS-GJ with Lap-GJ. Methods: Patients with GOO from 4 academic centers in 3 countries were included. Technical success was defined as successful creation of a gastrojejunostomy. Clinical success was defined as the ability to tolerate a diet postprocedure. Results: Data were collected on 54 patients. A total of 25 patients underwent EUS-GJ (male n=11, mean age 63.9 y) and 29 patients underwent Lap-GJ (male n=22, mean age 75.8 y). Technical success was achieved in 29 (100%) Lap-GJ group patients and 23 (88%) in the EUS-GJ group ( P =0.11). AEs occurred in 41% (n=12) of patients in the Lap-GJ group and 12% (n=3) in the EUS-GJ group ( P =0.0386). According to the Clavien-Dindo Classification, the Lap-GJ group AEs were grade I (n=4), grade II (n=5), grade III (n=2), and grade V (n=1); the EUS-GJ AEs were grade II (n=2) and grade V (n=1). Conclusions: Although the EUS-GJ group contained more complex patients, efficacy was similar between the groups. AEs were significantly lower in the EUS-GJ group. EUS-GJ is a safe and efficacious, minimally invasive option for patients with GOO.